2016
DOI: 10.1016/j.ijid.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Communicable disease surveillance and control in the context of conflict and mass displacement in Syria

Abstract: Five years into the crisis, some progress has been made in disease surveillance, but governance and coordination problems, variable immunization coverage, and the dynamic and indiscriminate nature of the conflict continue to pose a serious threat to population health in Syria and surrounding countries. The risk of major cross-border communicable disease outbreaks is high, and challenges for health in a post-conflict Syria are formidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 30 publications
2
70
0
Order By: Relevance
“…311 Although data regarding tuberculosis in Syria remains elusive, reports show a rapid rise of the disease in the country, which is still believed to only be a fraction of the actual burden. 311,312 After refugees leave their home country, the journey exacerbates their susceptibility to tuberculosis. Economic, social, and legal barriers increase the likelihood that tuberculosis will spread along the way and block access to care for those who contract it.…”
Section: Healthy People In Healthy Communitiesmentioning
confidence: 99%
“…311 Although data regarding tuberculosis in Syria remains elusive, reports show a rapid rise of the disease in the country, which is still believed to only be a fraction of the actual burden. 311,312 After refugees leave their home country, the journey exacerbates their susceptibility to tuberculosis. Economic, social, and legal barriers increase the likelihood that tuberculosis will spread along the way and block access to care for those who contract it.…”
Section: Healthy People In Healthy Communitiesmentioning
confidence: 99%
“…Ismail et al [30] reviewed the studies based on infectious diseases including polio, measles, and tuberculosis from 2005 to 2015. Communicable disease surveillance and control in the context of conflict and mass displacement in Syria have been focused.…”
Section: Emerging Infectious Diseases In Jordanmentioning
confidence: 99%
“…Displaced populations and refugee settlements are frequently exposed to TB risk factors, which can lead to increased transmission. An example is in Lebanon, where a 27% rise in TB incidence was attributed to the increase in the Syrian refugee population [6]. Likewise, a study in El Salvador reported the incidence rate of TB among internally displaced persons (IDPs) to be three times higher than the reported rate across the rest of the country [7].…”
Section: Introductionmentioning
confidence: 99%